Malondialdehyde levels are higher and glutathione levels are lower in preeclampsia than in normal pregnancies - Subandrate, Subandrate; Faisal, Mia Esta Poetri Afdal; Anggraini, Nurul Windi; Sinulingga, Sadakata (Universa Medicina, 2017)
BackgroundMaternal mortality rate is still a health problem in Indonesia. One major contributor to maternal mortality rate in Indonesia is preeclampsia. One widely accepted theory is that preeclampsia is caused by oxidative stress. Placental hypoxia or ischemia among preeclampsia patients is thought to be the cause of the formation of free radicals such as malondialdehyde (MDA), which decreases endogenous antioxidants such as glutathione (GSH). This study aims to ascertain the difference in plasma malondialdehyde and glutathione levels between healthy and preeclamptic pregnant women.MethodsThis was an observational analytic study of cross sectional design. Research subjects were 30Â  normal (healthy) pregnant women (NP), and 30 pre-eclamptic pregnant (PE) women. The measurement of plasma MDA and GSH levels was done at the Biochemistry and Molecular Biology laboratories, Faculty of Medicine, Sriwijaya University using Sigma-Aldrich MDA and GSH assay kits. Mann Whitney test was used to analyze the data. ResultsSubjects aged >35 years, with age of gestation >35 weeks and multipara was significantly higher in the PE group compared to the NP group (p=0.016; p=0.01 and p=0.36; respectively). MDA level was significantly higher in the PE group than in the NP group (p=0.002). In contrast, GSH level was significantly lower in the PE group than in the NP group (p=0.003).ConclusionMDA and GSH may reflect vascular complications of PE, and the ensuing increases in lipid peroxidation may play important pathogenic roles.